Antimalarial Evaluation of Quinoline-triazoleMn(I) and Re(I) PhotoCORMs - Ishmail, Fatima-Zahra (Department of Chemistry, 2020)
Malaria remains a disease of global health concern, as thousands of people fall victim to it annually. Despite the continuous development of new malaria chemotherapies, the parasite has adapted and mutated, conferring multi-drug resistant strains. The constant emergence of drug-resistant strains of malaria and the decrease in efficacy of most front-line treatments calls for the urgent development of new antimalarial chemotherapeutic drugs. It is of great importance to develop compounds that target resistant strains of malaria. Chloroquine is one of the most significantly studied antimalarials to date and its derivatives have been mainstays in malaria treatment. It has also been established that carbon monoxide (CO) is able to prevent Experimental Cerebral Malaria (ECM) (a severe form of malaria) through the prevention of haemoglobin oxidation.This study investigated the synthesis, characterization and biological evaluation as antiplasmodial agents of two new quinoline-1,2,4-triazole ligands and their respective Mn(I) and Re(I) tricarbonyl complexes. The two ligands differ in the presence of an extended amino-propyl chain conjugated to the quinoline scaffold, which has proven to confer greater antimalarial activity. Furthermore, the complexes were evaluated for their potential as photoCORMs (photo-induced Carbon Monoxide Releasing Molecules) and the CO-releasing effects on the antiplasmodial activity were evaluated. Two manganese tricarbonyl complexes (Mn-1 and Mn-2: contains amino-propyl chain) were evaluated for their CO-releasing properties upon photoexcitation with UV light at 365 nm. Both complexes release CO upon photoexcitation in DCM, DMSO/PBS and DMSO/growth medium solutions. The rate of CO-release is medium-dependent and the Mn-1 complex releases CO faster than the Mn-2 complex. The ligands and metal complexes were evaluated for their in vitro antiplasmodial activity against the NF54-chloroquine-sensitive and the K1-chloroquine-resistant strains of Plasmodium falciparum (P. falciparum). All tested compounds show good antiplasmodial activity with IC50 values in the low micromolar range. The manganese and rhenium analogues exhibit similar antiplasmodial activities, with IC50 values of 3.81 μM and 4.61 μM in the CQ sensitive strain respectively. Both complexes retain their activity in the CQ-resistant strain with resistance indices of 1. The ligand containing the amino-propyl chain (L2) exhibits the greatest antiplasmodial activity with IC50 values of 0.33 μM and 0.69 μM in the CQ-sensitive and -resistant strains respectively. The manganese complex thereof (Mn-2) has IC50 values of 0.54 μM and 1.16 μM in the CQ-sensitive and -resistant strains respectively. The antiplasmodial activity of the manganese complexes Mn-1 and Mn-2 increases 7- and 3- fold respectively upon photoexcitation at 365 nm in the K1-CQ-resistant strain. The increase in antimalarial activity exhibited upon light-induced CO-release presents a promising mechanism of combating drug-resistant P. falciparum. Mechanistic studies of these compounds indicate that they potentially work via β-hematin inhibition, with the metal complexes being greater inhibitors than CQ. Upon photo-induced CO-release, the β-hematin inhibition of complex Mn-1 increases drastically.